Tell Bleibil, Jordanien. Die Arbeiten des Jahres 2018 - Ahrens, Alexander (e-Forschungsberichte des DAI, 2019)
As part of the Wadi Shuʿaib Archaeological Survey Project (WSAS), excavations are carried out at the site of Tell Bleibil (Tall Bulaybil), located at the mouth of the alluvial fan of the Wadi Shuʿaib in the southern Jordan Valley, since 2017. In the campaign of 2018, test trenches at the site were excavated in order to expose Iron Age strata and to further substantiate the results obtained by soil sampling for botanical analysis and radiocarbon dating in 2017. The excavations conducted in 2018 uncovered a large stone foundation, which may have belonged to the settlement’s city wall during the Iron Age.